Godot 4 game development projects : build five cross-platform 2D and 3D games using one of the most powerful open source game engines - Bradfield, Chris (Packt Publishing Ltd., 2023)
The Godot 4 Game Development Projects book introduces the Godot game engine and its feature-rich 4.0 version. With an array of new capabilities, Godot 4.0 is a strong alternative to expensive commercial game engines. If you’re a beginner, this user-friendly book will help you learn game development techniques, while experienced developers will understand how to use this powerful and customizable tool to bring their creative visions to life. This updated edition consists of five projects with more emphasis on the 3D capabilities of the engine that will help you build on your foundation-level skills by showing you how to create small-scale game projects. Along the way, you’ll gain insights into Godot’s inner workings and discover important game development techniques that you can apply to your own projects. Using a straightforward, step-by-step approach and practical examples, this Godot book covers everything from the absolute basics to sophisticated game physics, animations, and much more. Upon completing the final project, you’ll have a strong foundation for future success with Godot 4.0 and be ready to develop a variety of games and game systems.